Closed loop value chain to achieve sustainable solution for tannery effluent. (10th March 2019) - Gupta, Sandeep Kumar; Gupta, Sanjeev
Abstract: The challenge of bringing down the high total dissolved solids (TDS) in raw tannery effluent up-to or below discharge standards, and making it reusable should be dealt sustainably. Thus, in order to tackle this challenge, the authors, in this paper, discuss about a closed loop integrated system using the philosophy of a sustainable industrial ecosystem design. In the closed loop tertiary treatment technology, the Reverse Osmosis (RO) reject evaporates in the poly house evaporator, leaving behind a salt collection/sediment bearing 14% moisture content, consisting primarily of 79 ppm phosphorus and 40% organic matter, which in turn is very useful for the compost. This approach of closed loop value chain is very unique and relevant in the present context for the leather industry.